Insights into the key roles of proteoglycans in breast cancer biology and translational medicine - Theocharis, A. D.; Skandalis, S. S.; Neill, T.; Multhaupt, H. A.; Hubo, M.; Frey, H.; Gopal, S.; Gomes, A.; Afratis, N.; Lim, H. C.; Couchman, J. R.; Filmus, J.; et al. (Biochim Biophys ActaBiochim Biophys Acta, 2015)
Proteoglycans control numerous normal and pathological processes, among which are morphogenesis, tissue repair, inflammation, vascularization and cancer metastasis. During tumor development and growth, proteoglycan expression is markedly modified in the tumor microenvironment. Altered expression of proteoglycans on tumor and stromal cell membranes affects cancer cell signaling, growth and survival, cell adhesion, migration and angiogenesis. Despite the high complexity and heterogeneity of breast cancer, the rapid evolution in our knowledge that proteoglycans are among the key players in the breast tumor microenvironment suggests their potential as pharmacological targets in this type of cancer. It has been recently suggested that pharmacological treatment may target proteoglycan metabolism, their utilization as targets for immunotherapy or their direct use as therapeutic agents. The diversity inherent in the proteoglycans that will be presented herein provides the potential for multiple layers of regulation of breast tumor behavior. This review summarizes recent developments concerning the biology of selected proteoglycans in breast cancer, and presents potential targeted therapeutic approaches based on their novel key roles in breast cancer.
Keywords: *Translational Research, Biomedical; breast cancer; Breast Neoplasms/*genetics/pathology; Decorin; Female; Gene Expression Regulation, Neoplastic; Glypicans; Humans; Molecular Targeted Therapy; Neovascularization, Pathologic/drug therapy/*genetics/pathology; Proteoglycans; Proteoglycans/antagonists & inhibitors/*biosynthesis/therapeutic use; Serglycin; Signal Transduction/genetics; Syndecans; Tumor Microenvironment/genetics